Media Coverage, Public Interest, and Support in the 2016 Republican Invisible Primary. Issue 2 (29th October 2018) - Reuning, Kevin; Dietrich, Nick
Abstract : Donald Trump's success in the 2016 presidential primary election prompted scrutiny for the role of news media in elections. Was Trump successful because news media publicized his campaign and crowded out coverage of other candidates? We examine the dynamic relationships between media coverage, public interest, and support for candidates in the time preceding the 2016 Republican presidential primary to determine (1) whether media coverage drives support for candidates at the polls and (2) whether this relationship was different for Trump than for other candidates. We find for all candidates that the quantity of media coverage had significant and long-lasting effects on public interest in that candidate. Most candidates do not perform better in the polls following increases in media coverage. Trump is an exception to this finding, receiving a modest polling bump following an increase in media coverage. These findings suggest that viability cues from news media contributed to Trump's success and can be influential in setting the stage in primary elections.